2009
DOI: 10.1007/s00134-009-1704-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of crystalloid and colloid infusion on the kidney in rodent sepsis

Abstract: None of the examined volume solution was inert to the kidney. In a CLP rodent sepsis model, animals infused with balanced crystalloid SteroIso exhibited the least effects on kidney function. Both hydroxyethyl starch 6% 130/0.4 and gelatin 4% derogated the kidney, whereas gelatin was more harmful when compared with hydroxyethyl starch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 32 publications
2
46
3
1
Order By: Relevance
“…34,35 HES and GEL were chosen because of controversies related to immunomodulatory effects 36 and kidney damage. 37 we used these particular colloids also because they are dissolved in acetate containing solutions. A modern HES solution of tetrastarch type has been chosen because it appears to be less associated with kidney injury than a pentastarch one in experimental endotoxemic shock.…”
Section: Choice Of Fluid Replacement Therapymentioning
confidence: 99%
“…34,35 HES and GEL were chosen because of controversies related to immunomodulatory effects 36 and kidney damage. 37 we used these particular colloids also because they are dissolved in acetate containing solutions. A modern HES solution of tetrastarch type has been chosen because it appears to be less associated with kidney injury than a pentastarch one in experimental endotoxemic shock.…”
Section: Choice Of Fluid Replacement Therapymentioning
confidence: 99%
“…Despite the poor evidence to justify its use, colloid solutions are frequently administered by clinical practitioners in order to obtain a faster optimization of the intravascular circulatory volume 5,6 . In contrast, colloid infusions have been shown to be detrimental to kidney function when compared to crystalloid infusions in a rodent model of sepsis 7 .…”
Section: Introductionmentioning
confidence: 86%
“…For HES 130/0.4, evidence from adequately conducted prospective clinical trials is still lacking to show that this compound has an improved safety profi le while nonprospectively derived data suggest that this may not be the case. An international survey of 1013 ICU patients needing fl uid resuscitation for shock states found that the incidence of ARF was comparable in patients receiving HES 130/0.4 and in those receiving older HES solutions (20/119, 16 A recent review cited 9 studies in adult patients as proof for the claims of improved renal safety of HES 130/0.4 [19], but these studies were inadequately designed for such a purpose, being: -a non-randomized observational study which did not specify the type of used HES solutions [50], -a non-controlled small observational study in volunteers [51], -a study which compared cumulative doses of 19 L HES 130/0.4 against 22 L HES 200/0.5 in 31 patients with brain injury and found no diff erence in renal function [52], -a comparison of HES 130/0.4 in two diff erent solvents [53], -two perioperative studies [54,55] comparing HES 130/0.4 with the synthetic colloid gelatin which can also impair renal function [8,56,57]. Th e remaining three studies from the surgical setting [58][59][60] compared HES 130/0.4 with normal saline or human albumin but were underpowered (mean sample size 37 patients), used small cumulative doses (mean 45.5 mL/kg, 50 mL/kg being the recommended maximal daily dose) and short observation periods (mean 34.7 hours).…”
Section: Ad 4) Are Newer Hes Solutions Safer?mentioning
confidence: 99%